Recovering method for TC4 titanium alloy residual materials - LI BOBO; PEI TENG; LIU YINQI; WANG FEI; LIU RUBIN; ZHU JUNJIE (2017)
The invention provides a recovering method for TC4 titanium alloy residual materials and relates to the technical field of titanium material machining. The to-be-treated TC4 titanium alloy residual materials are selected firstly, and surface impurities of the TC4 titanium alloy residual materials are cleared; then TC4 titanium plates are selected to be subjected to sizing for titanium residual loading box preparation; a certain mass of the TC4 titanium alloy residual materials with impurities being removed and aluminum thin plates prepared from aluminum coils are weighed; then alternative laying material distribution is conducted in a titanium residual loading box till box loading is completed; and the loading box which completes material distribution is sequentially subjected to smelting, solidifying, ingot pulling, cooling and machining, and then a product is manufactured. According to the recovering method for the TC4 titanium alloy residual materials, the problems that the shape of traditional titanium re